Evaluation on the willingness of migrants and native farmers to transfer farmland in resettlement areas and their coupled coordination relationships: perspectives for environmental and social sustainability - Chen, Shaojun; Yu, Danyang; Lei, Ming; Sun, Jie; Wang, Xin (Frontiers in Environmental Science, 2024)
The construction of water conservancy and hydropower projects often involves substantial land acquisition and resettlement. Land is a crucial means of production, playing a significant role in ensuring food security and protecting the ecological environment and social development. However, with the advancement of urbanization and changes in production methods, there has been a noticeable shift in the behavior of farmers on lands . Abandon land and reclaim wasteland in the host resettlement areas lead to low land-use efficiency, environmental degradation, and frequent geological disasters. It is important to evaluate migrants’ and native farmers’ willingness to transfer farmland in resettlement area and their coupled coordination relationships to realize the effective of land use . This study evaluated these by constructing an index system from personal and family characteristics, land resource endowment, characteristics of the external policy environment, and psycho-cognitive characteristics. The results showed that the coupling degree of the two was 0.999, while their coupling degree of coordination was 0.68. The relative development degree was 1.01. It showed that there was a strong correlation between migrants’ and native farmers' willingness, and they were in basic coordination phase. The two influenced each other, and reached a basic balanced state. Farmland can be transferred between migrants and native farmers to improve their livelihood, resettle migrants, improve land-use efficiency and reduce wasteland reclamation. This suggested the possibility of establishing a land transfer resettlement model based on the willingness of migrants and native farmers to achieve the resettlement areas environmental and social sustainability.